The Effect of Road Transportation Sector on the Socio-Economic Industry of a Local District of Nsukka Urban Area, Nigeria - Nwokocha, Victor; Chikadibia, Eze (Unisia, 2025)
Road transportation sector perform a crucial role in improving the socio-economic industry of an area. It provides accessibility and exchange of ideas, information, goods and services. Road transportation is important for economic development as it connects different places, people, and enhance agriculture, industry, and service sectors perform better. This research examined the effect of road transportation sector on the socio-economic development of a Local district of Nsukka Urban, Nigeria. The study adopted a survey research design. A questionnaire survey of 150 respondents served as the source of data collection, while percentages and simple statistics were used to analyse the data. The result showed that there is an overall positive view about the effect of road transportation on the socio-economic industry of the study area. It showed that there was a total average response and standard deviation score of 2.90 and 0.70 for the surveyed variables. This signified that road transportation influenced socio economic development of the study area. This paper recommends that more road be built to link other parts of the town to the urban area. This is because of its potentials in providing employment and sources of livelihood for people.